'A translator is but one player in the literary field who constantly has to make choices': A case study: Marriage/Ordeal (1963) by Gerard Walschap, translated by Alex Brotherton. (2nd January 2022) - Wolters, Irvin
ABSTRACT: The Stichting tot Bevordering van de Vertaling van Nederlands Letterkundig Werk (The Foundation for the Promotion of the Translation of Dutch Literary Works) was a state-funded quasi-governmental organization established in 1954 to oversee the translation of Dutch literary works into a variety of languages until 1989. One of The Foundation's first key projects was the development of a series of Dutch imaginative works translated into English, eventually called the Bibliotheca Neerlandica, that would implicitly redress the imbalance in the international reception of Dutch literature and its fine-art counterpart in the Dutch Golden Age of painting. The translator, Alex Brotherton, was commissioned by The Foundation to translate three of the volumes and I selected one of these as my case study to consider whether his translation choices always met with success. On comparing his translation with the source text, I highlighted four key areas which were to challenge him and considered his decisions when dealing with proper names, foreign words within a text, titles and his fidelity to the source text. Brotherton was not the only player in the 1960s literary field and I considered others including publishing companies, the copy-editor and press reviews to ascertain the level of influence they had on the final published work.